Impact of Generative Artificial Intelligence Dependency on the Mental Health of College Students: The Mediating Role of Cognitive Load - Jiawen Li (Asia Pacific Economic and Management Review, 2026)
To explore the impact mechanism of generative AI dependence on the mental health of college students, this study collected data using a questionnaire survey, constructed a relationship model between generative AI dependence, cognitive load, and mental health, and conducted empirical testing using structural equation modeling. The results show that generative AI dependence has a significant negative impact on the mental health of college students; generative AI dependence significantly increases cognitive load; and cognitive load plays a significant mediating role in the impact of generative AI dependence on the mental health of college students. Based on this, universities should guide students to use generative AI tools rationally to improve their information processing capabilities, reduce cognitive load during the learning process, and improve mental health education and support mechanisms to promote the coordinated development of generative AI applications and the mental health of college students.